An overview of unipolar charger developments for nanoparticle charging - Intra P. (2014)
Charging of nanoparticles is an important process in aerosol sizing. A unipolar charger is one of the most important upstream components in aerosol particle sizing and measurement systems by electrical mobility analysis. The aim of particle charging for an electrical mobility analyzer is to impose a known net charge distribution on the aerosol particles for each size. Charger performance depends on the extrinsic charging efficiency and stable operation. A well-designed unipolar charger should provide high extrinsic charging efficiency and stability that can be accurately determined for any given operating conditions. Depending on the mechanisms used to generate the ionized gas, the chargers can be classified into: (i) a corona discharge chargers, (ii) a radioactive chargers, and (iii) a photoelectric chargers. In this article, a brief overview on the development of existing unipolar aerosol chargers for nanoparticles is presented. Descriptions of the operating principles as well as detailed physical characteristics of these chargers, including the corona discharge, ionizing radiation, and photoelectron emission, are given. © Taiwan Association for Aerosol Research.